Efficiency of early weaned beef calves is not improved by restricting feed intake during 84-day growing phase - Bailey, E.A.; Preedy, G.W.; Pacheco, L.A.; Jaeger, John R.; Waggoner, Justin W.; Olson, K. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Early weaning can be used by cow-calf producers to reduce stocking rates by 20% to 30% during drought. Ranchers may be reluctant to wean early because of reduced calf weights and reduced revenue compared with weaning calves at conventional ages. To avoid revenue shortfalls, calves can be retained and grown before selling; however, grain prices are currently at unprecedented levels. Feeding grain-based diets to calves less than 125 days of age has been associated with excessive fat accumulation early in the feeding period and decreased carcass weights. Conversely, several researchers have noted marked improvements in feed efficiency when grain-based finishing diets were limit-fed. High feed costs and early fat deposition may be attenuated by limit-feeding a grainbased diet to early weaned calves. Our goal was to measure performance and efficiency of lightweight, early weaned beef calves during an 84-day postweaning growing phase when feed intakes were varied to achieve targeted gains of 1, 2, or 3 lb/day.
Keywords: Cattle; Feed intake; Cattle performance; Gain